Vincetoxicum pulneyensis (Asclepiadoideae; Apocynaceae), a new species from the Southern Western Ghats of India - Ramasubbu, Raju; Bechu, Punnen Abraham; Kalaiselvan, Karuppasamy; Anjana, Surendran (Phytotaxa, 2026)
Vincetoxicum pulneyensis, a new species of Apocynaceae, is described from Kodaikanal Wildlife Sanctuary, Dindigul district, Tamil Nadu, India. The newly collected Vincetoxicum specimen distinguishes itself from its closest relatives, V. balakrishnanii and V. cordifolium, through several key vegetative and reproductive characters. Vincetoxicum pulneyensis possesses a villous stem and hirtellous follicles; it contrasts with V. balakrishnanii, which typically exhibits a glabrous to puberulous stem and glabrous follicles. The velvety, ovate to ovate-lanceolate leaves with a mucronate apex differ from the cordate base and acuminate apex in V. cordifolium. The specimen is characterised by a longer peduncle and hirsute bracteoles, whereas they have shorter peduncles and glabrous or ciliate bracteoles in V. balakrishnanii and V. cordifolium. Also, the presence of an ovate-elliptic calyx lobe and a fusiform follicle with a persistent calyx provides a distinct morphological departure from the more linear-lanceolate calyx lobes and standard follicle shapes found in the other two closely allied taxa. These distinct morphological characters of this species allow us to describe a new species within Vincetoxicum for the flora of India.